Anti-thyroid antibodies in the relation to TSH levels and family history of thyroid diseases in young Caucasian women - Kocełak, Piotr; Owczarek, Aleksander J.; Wikarek, Agnieszka; Ogarek, Natalia; Oboza, Paulina; Sieja, Małgorzata; Szyszka, Anna; Rozmus-Rogóż, Izabela; Puzianowska-Kuźnicka, Monika; Olszanecka-Glinianowicz, Magdalena; Chudek, Jerzy (Frontiers in Endocrinology, 2022)
Background In young women, hypothyroidism is associated with impaired fertility, increased risk of pregnancy loss, premature delivery, and impaired infant neurodevelopment, justifying the need to recognize the risk of hypothyroidism in women of reproductive age. Thus, this study aimed at assessing the frequency of occurrence of antibodies against thyroid peroxidase (TPOAb) and thyroglobulin (TGAb) in young Caucasian women in connection with various confounders. Methods The cross-sectional study involved 366 women aged 18-40 years without a diagnosis of thyroid disease. The personal and family medical history was collected, body mass and height were measured and an ultrasound examination of the thyroid gland was performed. Thyrotropin (TSH), free thyroxine, and free triiodothyronine levels, as well as TPOAb and TGAb titers, were determined by ECLIA. Results Two cases of hyperthyroidism (0.5%) and 6 cases (1.6%) of subclinical hypothyroidism were detected. TPOAb was detected in 21 (5.7%) and TGAb in 31 (8.6%) and any of the antibodies in 42 (11.6%) women. Antibodies were more frequent in the subgroup with TSH levels ≥ 2.5 mIU/L than in the subgroup with lower TSH levels (15.5% vs 6.9%, respectively, p<0.05). Any anti-thyroid antibodies were also detected more frequently in the subgroup with TSH levels ≥ 2.5 mIU/L (18.3% vs 10.0%, respectively, p<0.05). Women with the presence of TGAb or seropositive for either TGAb or TPOAb or TPOAb and TGAb antibodies were more likely to have higher TSH levels (OR = 2.48 and OR = 2.02; respectively, p < 0.05 for both). A family history of any thyroid diseases increased the risk of any anti-thyroid antibodies positivity (OR = 1.94; p < 0.05). Conclusions The results of our study suggest that TSH ≥ 2.5 mIU/L and a family history of any thyroid diseases justify screening for anti-thyroid antibodies in women of reproductive age, although the occurrence of these antibodies in the majority of cases is not related to thyroid dysfunction.